2008
DOI: 10.1080/10428190802064917
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T-plastin, FoxP3 and other tumor-associated markers by leukemic T-cells of cutaneous T-cell lymphoma

Abstract: Peripheral blood cells from 28 patients with leukemic cutaneous T-cell lymphoma including 25 patients with Sézary syndrome were evaluated for expression of regulatory T-cell-associated markers (FoxP3, CD25, CTLA-4, neurophilin-1), T-cell activation markers (CD28 and its ligands B7.1 and B7.2) and NK cell-associated markers (NKG2D and its ligands MicA and Mic-B) using real-time quantitative polymerase chain reaction. T-plastin served as a positive genetic marker, and its expression correlated to blood tumor bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 89 publications
4
44
1
1
Order By: Relevance
“…2,[19][20][21][22][23]32 In accordance with previous studies, we found no significant expression of T-plastin transcript in the 78 healthy volunteers tested, in contrast to the recent data published by Oprea et al, where 5% of healthy donors expressed a T-plastin transcript in PBLs. 33 Several reports have previously claimed that T-plastin can serve as a positive genetic marker, and that its expression correlated to blood tumor burden.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…2,[19][20][21][22][23]32 In accordance with previous studies, we found no significant expression of T-plastin transcript in the 78 healthy volunteers tested, in contrast to the recent data published by Oprea et al, where 5% of healthy donors expressed a T-plastin transcript in PBLs. 33 Several reports have previously claimed that T-plastin can serve as a positive genetic marker, and that its expression correlated to blood tumor burden.…”
Section: Discussioncontrasting
confidence: 57%
“…33 Several reports have previously claimed that T-plastin can serve as a positive genetic marker, and that its expression correlated to blood tumor burden. 22 However, our data showed a wide range of T-plastin expression levels among CTCL cases and 1/4 patients did not present T-plastin transcript although they exhibited clinical characteristic of a well-characterized SS.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations